2019
DOI: 10.1002/ijc.32329
|View full text |Cite
|
Sign up to set email alerts
|

Integration of whole‐genome sequencing and functional screening identifies a prognostic signature for lung metastasis in triple‐negative breast cancer

Abstract: Lung metastasis is one of the leading causes of death for triple‐negative breast cancer (TNBC). We sought to characterize the genetic alterations underlying TNBC lung metastases by integrating whole‐genome sequencing and functional screening. Furthermore, we aimed to develop a metastasis‐related gene signature for TNBC patients to improve risk stratification. In this prospective observational study, we first conducted whole‐genome sequencing of paired primary tumor and lung metastasis from one TNBC patient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Ultimately, we identified five genes including ENY2 , GPAA1 , NDUFA4L2 , NEDD9 , and NRP1 as the variables in the multivariate Cox model. Notably, ENY2 was identified as a prognostic signature for lung metastasis in triple-negative breast cancer ( 24 ). Moreover, ENY2, one of the mRNA transcription and export complex subunits, was also observed to have a higher frequency of copy number alterations (CNAs) and a higher mRNA expression level in ovarian cancer ( 25 ), indicating that ENY2 might act as a cancer driver gene.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, we identified five genes including ENY2 , GPAA1 , NDUFA4L2 , NEDD9 , and NRP1 as the variables in the multivariate Cox model. Notably, ENY2 was identified as a prognostic signature for lung metastasis in triple-negative breast cancer ( 24 ). Moreover, ENY2, one of the mRNA transcription and export complex subunits, was also observed to have a higher frequency of copy number alterations (CNAs) and a higher mRNA expression level in ovarian cancer ( 25 ), indicating that ENY2 might act as a cancer driver gene.…”
Section: Discussionmentioning
confidence: 99%
“…A single mutation on microrchidia family CW-type zinc finger 2 (MORC2) promoted TNBC lung metastasis by regulating heterogeneous nuclear ribonucleoprotein M (hnRNPM)- mediated CD44 splicing, which indicated that the knockdown of hnRNPM might reduce lung metastatic potential of TNBC cells with mutant MORC2 [ 20 ]. Another research revealed that the overexpression of transcription and export complex 2 subunit (ENY2) could promote TNBC progression and lung metastasis both in vitro and in vivo [ 21 ]. Further mechanisms clarifying TNBC lung metastasis are certainly worth exploring, which may provide potential targets for new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor mutation burden is largely attributed to genomic instability. Genomic instability generates tumor heterogeneity, from which aggressive variants with strong metastatic ability can form secondary lesions ( 42 ). However, the association between mutations and neoantigen burdens of primary breast tumors and the outcomes of lung metastasis remains unknown.…”
Section: Discussionmentioning
confidence: 99%